2008
DOI: 10.1590/s0104-66322008000100019
|View full text |Cite
|
Sign up to set email alerts
|

Prediciton of high-pressure vapor liquid equilibrium of six binary systems, carbon dioxide with six esters, using an artificial neural network model

Abstract: -Artificial neural networks are applied to high-pressure vapor liquid equilibrium (VLE) related literature data to develop and validate a model capable of predicting VLE of six CO 2 -ester binaries (CO 2 -ethyl caprate, CO 2 -ethyl caproate, CO 2 -ethyl caprylate, CO 2 -diethyl carbonate, CO 2 -ethyl butyrate and CO 2 -isopropyl acetate). A feed forward, back propagation network is used with one hidden layer. The model has five inputs (two intensive state variables and three pure ester properties) and two outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 46 publications
(46 reference statements)
0
29
0
Order By: Relevance
“…The training process corresponds to the determination of the ANNs internal parameters (weights and Figure 2. Procedure for PR-EOS GNM modeling Source: Adapted from [23] bias of each neuron) by performing sensitivity analyses on an objective function, which is optimized by different methods. After calculation of the new weights, the fixed GNM weights were restored to their values by using a modified version of the Matlab algorithm (trainlm).…”
Section: Pr-eos Gray Box Neural Model Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The training process corresponds to the determination of the ANNs internal parameters (weights and Figure 2. Procedure for PR-EOS GNM modeling Source: Adapted from [23] bias of each neuron) by performing sensitivity analyses on an objective function, which is optimized by different methods. After calculation of the new weights, the fixed GNM weights were restored to their values by using a modified version of the Matlab algorithm (trainlm).…”
Section: Pr-eos Gray Box Neural Model Generationmentioning
confidence: 99%
“…Si-Maussa et al [23] focused in the VLE prediction of carbon dioxideesters mixtures and reported Absolute Relative Deviations in the order of 4.95% and 0.19% for pressure and mole fraction estimations, respectively. Similarly, Karimi and Yousefi [25] studied a VLE of four binary refrigerant systems.…”
Section: Fig 3 Andmentioning
confidence: 99%
“…Since ANN have the ability to extract from experimental data the highly non-linear and complex relationships between the variables of the problem without any detailed knowledge of the system (Si-Moussa et al, 2008;Khaouane et al, 2013) and, given the great amount of available experimental data in the study, it was decided to apply this approach. In this way, it was possible to extract useful information for making decisions without the need to have a theoretical model of process behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Direct measurement of precise experimental data is often difficult and expensive, while the second method, which includes a large number of equations of states and excess Gibbs free energy models, is tedious and involves a certain amount of empiricism to determine mixture constants, through fitting experimental data and using various arbitrary mixing rules, making it difficult to select the appropriate model for a particular case [9]. Thus due to the difficulties of experimental measurements and also their time-consuming and costly nature, it is desirable to develop predictive methods for estimating the phase behavior of these kinds of systems.…”
Section: Introductionmentioning
confidence: 99%
“…This method provides nonlinear function mapping of a set of input variables into the corresponding network output. ANNs can be applied for accurate VLE determination of polar and nonpolar components [9,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Basic theory and application to chemical problems of ANN with the back-propagation algorithm have been previously discussed in [48].…”
Section: Introductionmentioning
confidence: 99%